MicroRNA-203 Expression as Potential Biomarker for Lupus Nephritis [Corrigendum] - Setyawan Y; Susianti H; Sulistyarti H; Khrisna MB; Mayashinta DK; Fitri LE; Samsu N (International Journal of Nephrology and Renovascular Disease)
Setyawan Y, Susianti H, Sulistyarti H, et al. Int J Nephrol Renovasc Dis. 2025;18:53—58. The authors have advised there is an error in affiliation 1 on page 53. The text “Doctoral Program in Biomedical Science” should read “Doctoral Program in Medical Sciences”. The authors apologize for this error.